Aeromonas hydrophila suppresses complement pathways via degradation of complement C3 in bony fish by metalloprotease. Issue 94 (November 2019) - Chen, Dan-Dan; Li, Ji-Hong; Yao, Yuan-Yuan; Zhang, Yong-An
Abstract: Aeromonas hydrophila is a pathogen that causes high mortality in the grass carp. The complement system, as a frontline defence of innate immunity, plays an important role in the immune response against pathogens. However, the immunity evasion mechanism of A. hydrophila against the complement system of grass carp remains unclear. In this study, we described an additional mechanism used by A. hydrophila GD18 to evade the complement system and survive in grass carp serum. First, A. hydrophila evaded the bactericidal activity of grass carp serum. Second, the haemolytic activity assays showed that A. hydrophila obviously suppressed the alternative pathway, which depended on preventing the formation or disabling the function of the membrane-attack complex (MAC). Further research indicated that A. hydrophila targeted complement C3, the central component of the three complement pathways, and degraded it in the grass carp serum, leading to the inhibition of the complement pathways, which resulted in the serum-resistance of A. hydrophila. Furthermore, cleavage analyses showed that extracellular proteases (ECPases) of A. hydrophila efficiently cleaved purified C3 as well as C3 in grass carp serum. Finally, protease inhibitor studies and mass spectrum analysis identified the secreted metalloprotease elastase (AhE), which was present in large amounts in crude ECPases, as the central molecule responsible for C3 cleavage. Compared to wild strain GD18, the AhE knockout, Δ ahe was dramatically reduced in the ability of serum resistance. Our findings suggested that A. hydrophila escaped serum-killing by suppressing the complement pathways via the degradation of complement C3 in bony fish, which was related to secreted metalloproteases. Highlights: A. hydrophila evades the bactericidal activity of grass carp serum. A. hydrophila targets complement C3, the central component of the three complement pathways, and degrades it in the serum. The secreted metalloprotease elastase (AhE) is involved in the A. hydrophila- mediated inactivation of C3. Compared to wild strain GD18, the AhE knockout, Δ ahe was dramatically reduced in the ability of serum resistance.